2011
DOI: 10.1089/neu.2009.1168
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Hospital Care Management of a Potential Spinal Cord Injured Patient: A Systematic Review of the Literature and Evidence-Based Guidelines

Abstract: An interdisciplinary expert panel of medical and surgical specialists involved in the management of patients with potential spinal cord injuries (SCI) was assembled. Four key questions were created that were of significant interest. These were: (1) what is the optimal type and duration of pre-hospital spinal immobilization in patients with acute SCI?; (2) during airway manipulation in the pre-hospital setting, what is the ideal method of spinal immobilization?; (3) what is the impact of pre-hospital transport … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
60
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(62 citation statements)
references
References 55 publications
1
60
0
1
Order By: Relevance
“…[11]  Delayed transport, increasing time to definitive care. [19]  Confounding clinical examination and vital sign recordings. [20] Hauswald, [21] and the authors of three systematic reviews, [18,22,23] conclude that phSI may be contributing to patient morbidity and mortality.…”
Section: Side Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…[11]  Delayed transport, increasing time to definitive care. [19]  Confounding clinical examination and vital sign recordings. [20] Hauswald, [21] and the authors of three systematic reviews, [18,22,23] conclude that phSI may be contributing to patient morbidity and mortality.…”
Section: Side Effectsmentioning
confidence: 99%
“…[25,26] Conversely, Ahn and Singh found that 8% of vertebral column injuries were not immobilised and no clinical consequences resulted. [19] Gerrelts et al found that patients with a delayed diagnosis of cervical spine fracture did not develop permanent neurological deficits. [27] There were no case-control studies that directly compared the outcomes of patients who were immobilised against those that were not.…”
Section: Benefitsmentioning
confidence: 99%
“…As an example, Perry et al [6] reported relative neck motions associated with horizontal vibration that were deemed clinically significant by a neuroscientist for a potential contribution to spinal cord injury. Ahn et al [7] conducted a comprehensive literature review on the management of pre-hospital care of potential spinal cord injury patients, including the ideal methods for spinal immobilization. The authors recommended the use of the spinal board, cervical collar, and head immobilization during the pre-hospital setting.…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps related to care, length of acute care stay has also been shown to affect functional outcomes after SCI, and could provide further insight. 9,10 Regarding inclusion/exclusion criteria, the authors provided valid reasoning for the inclusion of specific injury characteristics (limiting heterogeneity and ceiling effects in recovery), though no reason was given for the exclusion of individuals in prior care. Second, patients who were rehospitalized for unspecified infectious or parasitic diseases during follow-up were also excluded, and a justification was also not provided.…”
mentioning
confidence: 99%